Time–frequency analysis for delineating gas hydrates and free gas in the Mahanadi offshore, India. Issue 1 (2nd January 2022) - Kumar, Jitender; Sain, Kalachand; Arun, K. P.
Abstract : The present work demonstrates a case study in the Mahanadi offshore basin in the eastern margin of India, where gas hydrates have been delineated by seismic experiment, mainly by identifying a bottom simulating reflector or BSR on seismic section, based on its characteristic features. The BSR represents an acoustic impedance contrast between the high-velocity gas hydrates bearing sediments above and low-velocity gas-bearing or water-saturated sediments below. At some places along the continental margins of the world, the BSR has not been identified but gas hydrates were recovered by drilling, whereas at some other places BSR was identified but no gas hydrates were found. Thus, we need to find out an attribute that can be used to characterise gas hydrates and free gas reservoirs. The purpose of this work is to demonstrate this through spectral decomposition in the time–frequency domain. The study based on continuous wavelet transform (CWT) approach, which uses a mathematical mother wavelet, shows the illuminated zone with higher energy low-frequency anomaly, associated with free gas below the BSR. The study demonstrates that the CWT technique provides higher spectral-spatial resolution than that obtained by the short-term Fourier transform technique.